2019
DOI: 10.3390/met9121247
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Primary Carbides in a Commercial-Sized Electroslag Remelting Ingot of H13 Steel

Abstract: The characteristics of primary carbides in a commercial-sized (one ton) electroslag remelting (ESR) ingot of AISI H13 steel were investigated. The interaction between the primary carbides and inclusions was also clarified. The results indicate that there are two types of primary carbides, V-rich and Mo-rich primary carbides, in the H13 ESR ingot. The quantity, the area fraction, and the size of the two primary carbides tend to decrease from the center of the H13 ESR ingot to the outer surface. Additionally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…As shown in Figure 6 , the Al 2 O 3 and MnS inclusions are commonly located in the core of the primary carbide (including a V‐rich primary carbide (V‐PC) and Mo‐rich primary carbide (Mo‐PC)). We showed that the Al 2 O 3 and MnS inclusions have low disregistries with the primary carbides in H13 steel, [ 12,34 ] which indicates that the Al 2 O 3 and MnS inclusions could act as nucleation cores of primary carbides to generate large complex precipitates, as depicted in Figure 6. By modifying the Al 2 O 3 and MnS inclusions into Ce 2 O 3 or Ce 2 O 2 S, the formation of the large complex precipitates can be prevented due to the high disregistries between Ce 2 O 3 /Ce 2 O 2 S inclusions and primary carbides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6 , the Al 2 O 3 and MnS inclusions are commonly located in the core of the primary carbide (including a V‐rich primary carbide (V‐PC) and Mo‐rich primary carbide (Mo‐PC)). We showed that the Al 2 O 3 and MnS inclusions have low disregistries with the primary carbides in H13 steel, [ 12,34 ] which indicates that the Al 2 O 3 and MnS inclusions could act as nucleation cores of primary carbides to generate large complex precipitates, as depicted in Figure 6. By modifying the Al 2 O 3 and MnS inclusions into Ce 2 O 3 or Ce 2 O 2 S, the formation of the large complex precipitates can be prevented due to the high disregistries between Ce 2 O 3 /Ce 2 O 2 S inclusions and primary carbides.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] Dendritic segregation in the H13 steel results in the generation of primary carbides. [12] In contrast, dendritic segregation is inherited after the hot forming process and creates banded structures, which have an adverse effect on the isotropy of the steel. [13,14] The banded structures and primary carbides would negatively affect the toughness of the H13 steel and reduce its service life.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to add nanoparticles to liquid steel [35,47,61,62] due to the large specific gravity difference between liquid steel and nanoparticles [63][64][65][66][67]. Nanoparticles easily adsorb contamination and thus affect the strengthening effect [68,69]. In addition, the surface energy of nanoparticles is relatively high, so they are easy to agglomerate and difficult to disperse [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of Ti element is inevitable in molten steel during the actual smelting process because of the introduction of the alloying elements. Researchers have found large Ti-containing primary carbides in both as-cast H13 steel and H13 bars after heat treatment [16][17][18][19][20]. Large primary carbides as well as large Ti-containing carbonitride particles will act as a crack source, thus reducing the service life of H13 steel [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of different Ti contents on primary carbides' behavior was not studied by Xie. Moreover, most researchers have ediscussed the characteristics of primary carbides from a two-dimensional perspective [16][17][18][19][20]. Few researchers have systematically studied the characteristics of the primary carbides in H13 steel from the three-dimensional perspective.…”
Section: Introductionmentioning
confidence: 99%